PET imaging of [11C]PBR28 in Parkinson’s disease patients does not indicate increased binding to TSPO despite reduced dopamine transporter binding - Varnäs, Katarina; Cselényi, Zsolt; Jucaite, Aurelija; Halldin, Christer; Svenningsson, Per; Farde, Lars; Varrone, Andrea (European journal of nuclear medicine and molecular imaging, 2019)
Purpose To examine the hypothesis that cerebral binding to the 18 kDa translocator protein (TSPO), a marker of microglia activation, is elevated in Parkinson’s disease (PD), and to assess the relationship between brain TSPO binding and dopaminergic pathology in PD. Methods The radioligand [ 11 C]PBR28 was used for quantitative assessment of brain TSPO in 16 control subjects and 16 PD patients. To analyse the relationship between dopaminergic pathology and brain TSPO binding, PET studies of the dopamine transporter (DAT) were undertaken in PD patients using the DAT radioligand [ 18 F]FE-PE2I. The total distribution volume of [ 11 C]PBR28 was quantified in nigrostriatal regions, limbic cortices and thalamus, and the binding potential of [ 18 F]FE-PE2I was quantified in nigrostriatal regions. Results Based on genotype analysis of the TSPO rs6971 polymorphism, 16 subjects (8 control subjects and 8 PD patients) were identified as high-affinity binders, and the remaining subjects were identified as mixed-affinity binders. A two-way ANOVA showed a strong main effect of TSPO genotype on the cerebral binding of [ 11 C]PBR28, whereas no statistically significant main effect of diagnostic group, or a group by genotype interaction was found for any of the regions analysed. [ 18 F]FE-PE2I PET studies in patients indicated a marked reduction in nigrostriatal binding to DAT. However, no correlations between the binding parameters were found for [ 11 C]PBR28 and [ 18 F]FE-PE2I. Conclusion The findings do not support the hypothesis of elevated cerebral TSPO binding or a relationship between TSPO binding and dopaminergic pathology in PD.